"You Look Fine!": Ableist Experiences by People With Invisible Disabilities. Issue 4 (November 2018) - Kattari, Shanna K.; Olzman, Miranda; Hanna, Michele D.
Much existing research on ableism focuses on individuals whose disabilities are more apparent to others. Using a phenomenological approach, this study interviewed 14 participants, exploring how people with "invisible" physical disabilities experience ableism. In addition to multiple examples of microaggressions, emergent themes included the policing of bodies, tension in roles, a desire for justice, and internalized ableism. Many of the participants recounted experiences of having bodies and actions policed by others, and several struggled with their role in educating others about policies, needs, and accommodations. The theme of desire for justice included frustration at having to educate others, the energy this education took, and the desire for overarching justice regarding ableism. The theme of internalized ableism reflected both explicit experiences of individuals sharing their self-judgment and ableist statements during interviews. These findings indicate the need for a more nuanced understanding by social workers of how ableism is experienced by those with invisible disabilities as well as additional research on how to support these members of the community.